Respon Siswa terhadap Penggunaan Aplikasi Envemath untuk Meningkatkan Kemampuan Berpikir Kritis dan Minat Belajar - Novitaningsih, Yossi; Marhaeni, Nafida Hetty (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The use of the EnveMath mathematics learning application to improve students' critical thinking skills and learning interests. This type of research is quantitative descriptive research. The data used in this study is data obtained from student response questionnaires. The sample technique used is purposive sampling where the class with the lowest average Final Semester Assessment (PAS) is used as a large-scale trial class, while the class with the highest average Final Semester Assessment (PAS) is used as a small-scale trial class. The sample used was class VIII C as many as 34 students as a large-scale trial and class VIII B as many as 17 students as a small class trial. The data collection technique uses a questionnaire that contains statement items including usefulness, ease of use, ease of learning, and satisfaction. The data analysis technique used is a qualitative data analysis technique. The results showed that the response of students in the small-scale trial was in the good category with an average of 112.4 and in the large-scale trial was in the good category with an average of 114.3. Thus, it can be concluded that the EnveMath learning application as a mathematics learning medium has received a positive response from students and is practically used as a mathematics learning medium.